Pancreas, islet and stem cell transplantation for diabetes - Hakim, Nadey S., 1958- (Oxford : Oxford University Press, 2010)
This resource reflects recent advances in the field of pancreas transplantation, especially the increasing number of islet transplantations and the growing interest in stem cell research applicable to this condition. It provides an authoritative account on the current status of the whole organ pancreas transplantation and islet and pancreatic stem cell transplantation.
Previous ed. published as Pancreas and islet transplantation. 2002.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Pancreas -- Transplantation; Islands of Langerhans -- Transplantation